What are the factors associated with sarcopenia-related variables in adult women with severe obesity? - Erika Aparecida Silveira; Jacqueline Danesio de Souza; Annelisa Silva e Alves de Carvalho Santos; Andrea Batista de Souza Canheta; Valéria Pagotto; Matias Noll (BMC, 2020)
Abstract Background Understanding the association between sarcopenia-related variables and several risk factors may help to implement interventions aimed at preventing its occurrence by reducing or controlling the identified risk factors. Although changes in body composition occur in both sexes, in women, muscle loss is accentuated due to decreased estrogen levels following menopause. This study aims to determine the factors associated with sarcopenia-related parameters in middle-aged women identified with class II/III obesity (body mass index [BMI] ≥ 35 kg/m2). Methods The study included 104 women with severe obesity (40.23 ± 8.49 years) with an average body fat percentage of 52.45 ± 4.14%. Sarcopenia was assessed using total appendicular skeletal muscle mass (ASMM), appendicular skeletal muscle mass index (ASMMI), and appendicular skeletal muscle mass adjusted by BMI (ASMM/BMI) as evaluated using dual energy X-ray absorptiometry (DXA). Hand grip strength (HGS) and HGS adjusted by BMI (HGS/BMI) were evaluated using dynamometry. Functional performance was assessed using the walking speed test (WS). The explanatory variables were age, lifestyle, comorbidities, food consumption, and metabolic parameters. A multivariate linear regression was performed. Results Factors associated with sarcopenia-related variables in 104 severely obese women with a mean BMI of 43.85 kg/m2 were as follows: ASMMI negatively correlated with serum levels of tetraiodothyronine (T4) and tobacco use; ASMM/BMI negatively correlated with age, serum T4 levels, and diabetes; ASMM negatively correlated with T4 serum levels and diabetes; HGS negatively correlated with age and hypercholesterolemia, and positively correlated with low-density lipoprotein cholesterol (LDL-c); HGS/BMI negatively correlated with age and hypercholesterolemia and positively correlated with LDL-c; and WS negatively correlated with hypothyroidism and diabetes. Conclusion In severely obese women, muscle mass and function were inversely associated with age, smoking status, endocrine parameters, hypercholesterolemia, and comorbidities such as diabetes. Thus, the results of this investigation are relevant in supporting the development of clinical interventions to aid in the prevention of sarcopenia in adult women with severe obesity.